Auslegung von Verstärkungen ermüdungsgeschädigter Stahlbauteile mit aufgeklebten Faserverbundwerkstoffen - Kasper, Yann J. (Berichte zum Stahl- und Leichtbau, 2024)
Within the scope of the present work, extensive experimental and numerical investigations are carried out on the crack propagation behaviour in steel plates under cyclic loading, which have been reinforced with adhesively bonded CFRP lamellas, as well as on the load-bearing and failure behaviour of CFRP-steel double-lap joints. Based on the results, a fracture mechanics engineering procedure for estimating the remaining service life of CFRP-reinforced steel plates is developed and validated.